2017
DOI: 10.1111/gtc.12472
|View full text |Cite
|
Sign up to set email alerts
|

Knock‐in strategy at 3′‐end of Crx gene by CRISPR/Cas9 system shows the gene expression profiles during human photoreceptor differentiation

Abstract: Fluorescent reporter gene knock-in induced pluripotent stem cell (iPSC) lines have been used to evaluate the efficiency of differentiation into specific cell lineages. Here, we report a knockin strategy for the generation of human iPSC reporter lines in which a 2A peptide sequence and a red fluorescent protein (E2-Crimson) gene were inserted at the termination codon of the cone-rod homeobox (Crx) gene, a photoreceptor-specific transcriptional factor gene. The knock-in iPSC lines were differentiated into fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…MELAS patient-derived (A24#1–3) and control human iPSCs (454E2, RIKEN BRC, Japan) [ 38 ] were cultured in a feeder-free condition as described previously [ 27 ]. Cells were maintained in Nutristem (Riprocell, Japan) on Matrigel (human embryonic stem cell-qualified Matrigel, BD, NJ, USA) coated 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MELAS patient-derived (A24#1–3) and control human iPSCs (454E2, RIKEN BRC, Japan) [ 38 ] were cultured in a feeder-free condition as described previously [ 27 ]. Cells were maintained in Nutristem (Riprocell, Japan) on Matrigel (human embryonic stem cell-qualified Matrigel, BD, NJ, USA) coated 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we generated MELAS patient-derived iPSC lines harboring the mtDNA A3243G mutation and expressing high levels of the mutant mtDNA. We documented metabolic changes in MELAS iPSCs, demonstrated the phenotype of the RPE differentiated from these iPSCs [ [25] , [26] , [27] , [28] , [29] ], and analyzed the protective effects of taurine. The undifferentiated pluripotent stem cells (PSCs) possess functional OXPHOS machinery; however, it is decoupled from glycolysis, which is the major energy source in PSCs, similarly to the situation in cancer cells [ [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
“…On a different note, CRISPR/Cas technology in iPSCs has been used for fluorescent reporter gene knock-in at the termination codon of the cone-rod homeobox ( Crx ) gene, a photoreceptor-specific transcription factor gene. This allows the real-time monitoring of photoreceptor differentiation [ 158 ], demonstrating the interest of this technology also for fundamental research.…”
Section: Ex Vivo Gene Correction and Cell-based Therapymentioning
confidence: 99%
“…For instance, we and others have shown that following subretinal transplantation iPSC‐derived photoreceptor precursors cells are able to restore retinal function in animal models of retinal degenerative blindness 1‐10 . Following decades of development, the vast majority of the differentiation protocols reported faithfully recapitulate normal retinal development, which means that they give rise to each of the different cell types found in the retina 10‐40 . For therapeutic photoreceptor cell replacement, enrichment of photoreceptor precursor cells away from the unwanted cell types (ie, retinal ganglion cells, bipolar inter neurons, retinal pigmented epithelial [RPE] cells, etc) will be desirable.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Following decades of development, the vast majority of the differentiation protocols reported faithfully recapitulate normal retinal development, which means that they give rise to each of the different cell types found in the retina. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 For therapeutic photoreceptor cell replacement, enrichment of photoreceptor precursor cells away from the unwanted cell types (ie, retinal ganglion cells, bipolar inter neurons, retinal pigmented epithelial [RPE] cells, etc) will be desirable.…”
Section: Introductionmentioning
confidence: 99%